Induction and therapy of autoimmune diabetes in the non-obese diabetic (NOD/Lt) mouse by a 65-kDa heat shock protein. - Elias, D (1990)
Insulin-dependent diabetes mellitus is caused by autoimmune destruction of the insulin-producing beta cells of the pancreas. The results described here indicate that a beta-cell target antigen in non-obese diabetic (NOD/Lt) mice is a molecule cross-reactive with the 65-kDa heat shock protein (hsp65) of Mycobacterium tuberculosis. The onset of beta-cell destruction is associated with the spontaneous development of anti-hsp65 T lymphocytes. Subsequently hsp65 cross-reactive antigen becomes detectable in the sera of the prediabetic mice and some weeks later anti-hsp65 antibodies, anti-insulin antibodies, and anti-idiotypic antibodies to insulin antibodies become detectable. The hsp65-cross-reactive antigen, the autoantibodies, and the T-cell reactivity then decline with the development of overt insulin-dependent diabetes. The importance of hsp65 in the pathogenesis of insulin-dependent diabetes was confirmed by the ability of clones of anti-hsp65 T cells to cause insulitis and hyperglycemia in young NOD/Lt mice. Moreover, hsp65 antigen could be used either to induce diabetes or to vaccinate against diabetes, depending on the form of its administration to prediabetic NOD/Lt mice. Other antigens such as the 70-kDa heat shock protein (hsp70) had no effect on the development of diabetes.